Case Report: Ascending hope—urgent endovascular repair of aortic pseudoaneurysm - Ronen, Daniel; Planer, David; Beeri, Ronen; Korach, Amit; Elbaz Greener, Gabby; Rahamim, Eldad (Frontiers in Cardiovascular Medicine, 2025)
We report a case of an ascending aortic pseudoaneurysm that developed as a complication of coronary artery bypass graft surgery and was managed with percutaneous endovascular repair. A 59-year-old man presented 9 months after bypass surgery, with complaints of dysphagia and shortness of breath. Computed tomography and echocardiography demonstrated a pseudoaneurysm of the ascending aorta. The patient's overall condition put him at a very high perioperative risk, prohibiting surgical intervention. However, the patient deteriorated clinically and suffered cardiac arrest, requiring repeated resuscitation efforts. In need of an urgent solution, the heart team recommended the interventional cardiology team perform a percutaneous endovascular repair, which resulted in significant hemodynamic improvement. Patients' clinical improvement allowed the surgical team to conduct a sternotomy to remove substantial mediastinal blood clots and place a bovine patch on a residual aortic leak. After recovery, the patient was discharged home and at 1-year follow-up is doing well. This case demonstrates the feasibility of percutaneous endovascular treatment in medical emergencies of the ascending aorta, when standard surgical treatment carries unacceptable risk.